PENGARUH KOMPOSISI BAHAN BAKU TERHADAP BIAYA BAHAN BAKU, HARGA POKOK PRODUKSI, DAN PRODUKTIVITAS MASSA BODI BL PADA UPT PSTKP BALI-BPPT TAHUN 2014 - I Nyoman Normal; Wiryawan Suputra Gumi (Forum Manajemen STIMI Handayani Denpasar, 2015)
The aims of this research that relate raw material composition intoproduction process of BL (BL1X, BL2, BL1, BL3) stoneware were: (1) To know theinfluence of raw material composition to raw material cost loading stoneware BL;(2) To know the influence of raw material composition to cost of good manufacturedcalculation; and (3) To know the influence of raw material composition toproductivity.The research results shew that: (1)The increasing of raw material composition kalblend clay on production process of BL stoneware could decrease raw material cost of BL stoneware. For that, if the UPT PSTKP Bali want to decrease raw materialcost of BL stoneware, so it could act by increase composition of kalblend clay in thatraw material mixing; (2) The increasing of raw material composition kalblend clayon production process of BL stoneware could decrease cost of goods manufacturedBL stoneware. For that, if the UPT PSTKP Bali want to decrease cost of goodsmanufactured BL stoneware, so it could act by increase composition of kalblend clayin that raw material mixing; and (3) The increasing of raw material compositionkalblend clay on production process of BL stoneware could decrease productivityof BL stoneware. For that, if the UPT PSTKP Bali want to decrease cost of goodsmanufactured BL stoneware, so it could act by increase composition of kalblend clayin that raw material mixing